Storage structures and aflatoxin content of maize in five agroecological zones of Nigeria - Udoh, J.M.; Cardwell, K.F.; Ikotun, T. (Elsevier, 2000)
A survey was conducted in 1994 to describe the maize storage systems, quantify the aflatoxin levels in these storage systems, and identify the main problems of maize storage recognized by both men and women farmers in five agroecological zones in Nigeria. Maize storage in bags was the most common among all farmers. The clay rhumbu was used in 4 out of 5 agroecological zones by both male and female farmers. The woven oba was found only in the southern Guinea savanna and was used predominantly by women. Only 13% of the male farmers in the southern Guinea savanna and none in the other zones stored in an improved crib while no female farmers across all the zones used the crib system of storage. Male and female farmers across all the zones identified insect infestation, and fungal and rodent attack as the main problems in their stored maize. Insect infestation was reported by 83% of the female farmers in the southern Guinea savanna zone who stored maize in bags. The highest fungal attack on stored maize was reported by 71% of the male farmers who stored maize in bags in the humid forest zone, while 75% of the male farmers who stored in bags in the Sudan savanna zone complained of rodent attack. Across all zones, farmers of both genders identified insects as the most common storage problem. Farmers who reported insect problems were significantly more likely to have aflatoxin in their stores. The highest zonal mean aflatoxin level of 125.6 ?g/kg was obtained from maize samples provided by male farmers in the Sudan savanna zone who stored maize in bags or in a rhumbu. Across the storage systems, 33% were contaminated with detectable levels of aflatoxin. No aflatoxin was detected in the storage systems of male or female farmers in the northern Guinea savanna zone in 1994.